C1QTNF3 in the murine ovary and its function in folliculogenesis. Issue 4 (April 2018) - Mao, Zhoufei; Yang, Liuhong; Lu, Xiaosheng; Tan, Anni; Wang, Yuxia; Ding, Fei; Xiao, Luanjuan; Qi, Xufeng; Yu, Yanhong
Abstract : C1q/tumor necrosis factor-related protein 3 (C1QTNF3) is a novel adipokine with modulating effects on metabolism, inflammation and the cardiovascular system. C1QTNF3 expression levels in the sera and omental adipose tissues of women with PCOS are low compared to control subjects. However, the expression and function of C1QTNF3 in the ovary has not previously been examined. Here, we assessed the expression patterns of C1qtnf3 in the ovary and explored its role in folliculogenesis. The C1qtnf3 transcript abundance was higher in large follicles than in small follicles and was under the influence of gonadotropin. C1QTNF3 was detected mainly in the granulosa cells and oocytes of growing follicles and modestly in the granulosa cells of atretic follicles and in luteal cells. Excess androgen significantly decreased C1QTNF3 expression in the ovaries in vivo and in granulosa cells in vitro . Recombinant C1QTNF3 protein accelerated the weight gain of ovarian explants and the growth of preantral follicles induced by follicle stimulating hormone (FSH) in vitro . The stimulatory effect of C1QTNF3 on ovarian growth was accompanied by the initiation of AKT, mTOR, p70S6K and 4EBP1 phosphorylation, an increase in CCND2 expression and a reduction in cleaved CASP3 levels. Moreover, the addition of C1QTNF3 accelerated proliferation and reduced activated CASP3/7 activity in granulosa cells. In vivo, the ovarian intrabursal administration of the C1QTNF3 antibody delayed gonadotropin-induced antral follicle development. Taken together, our data demonstrate that C1QTNF3 is an intraovarian factor that promotes follicle growth by accelerating proliferation, decelerating apoptosis and promoting AKT/mTOR phosphorylation.